1980
DOI: 10.3177/jnsv.26.375
|View full text |Cite
|
Sign up to set email alerts
|

Serum lipid levels in iron deficiency anemia and effects of various treatments.

Abstract: SummaryEffects of anemia on serum total cholesterol and tri glyceride levels were studied in Sri Lanka. In subjects with hemoglobin (Hb) levels of less than 9.0g/100ml, there was a significant relationship between Hb and cholesterol levels (r=0.53). This relationship was not seen in subjects with Hb levels equal to, or greater than, 9.0g/100ml. Triglyceride levels were independent of Hb levels. Total cholesterol levels were elevated following an increase in Hb levels by transfusion and iron treatment. It was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
1

Year Published

1982
1982
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 13 publications
2
5
1
Order By: Relevance
“…The findings of Ohira et al. () and Cunnane and McAdoo () were similar. On the other hand, Guthrie et al.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The findings of Ohira et al. () and Cunnane and McAdoo () were similar. On the other hand, Guthrie et al.…”
Section: Discussionsupporting
confidence: 65%
“…Bristow-Craig et al (1994) demonstrated that higher levels of iron in a diet increased cholesterol in the plasma of rats. The findings of Ohira et al (1980) and Cunnane and McAdoo (1987) were similar. On the other hand, Guthrie et al (1974) and Amine et al (1976) observed hyperlipidemia in rats and chickens fed on diets deficient in iron.…”
Section: Discussionsupporting
confidence: 53%
“…Our data do not agree with numerous other publications which report an association between iron deficiency anemia and hyperlipidemia [1][2][3][4][5][6][7]. Differences in type and levels of dietary fat, fiber content, and levels of vitamins and minerals could affect degree of anemia and hyperlipidemia [33].…”
Section: Discussioncontrasting
confidence: 99%
“…Severe iron deficiency anemia produced by either dietary means or by acute hemolysis is associated with marked lipemia in both animal models [1][2][3] and humans [4][5][6][7]. The mechanisms involved in the etiology of hyperlipidemia in iron-deficiency anemia are not understood fully.…”
Section: Introductionmentioning
confidence: 99%
“…These results are consistent with the reports of investigators , demonstrating that dietary iron supplementation Licensed Under Creative Commons Attribution CC BY increases plasma lipids in iron deficient girls and in rats. Ohira et al [35] found that total cholesterol concentrations were elevated following an increase in haemoglobin levels by transfusion and iron treatment. They also reported that the concentration of red blood cells might affect cholesterol synthesis or its mobilization from tissue to plasma.…”
Section: Discussionmentioning
confidence: 99%